The Effectiveness of The Use of E-Commerce and Digital Payment on Brand Awareness of Private Regional Drinking Water Companies (PDAM) - Dedi Dedi; Farida Frihatini; Yadi Kusnadi (Jurnal Manajemen Indonesia, 2024)
Customer satisfaction is the main focus of the company to increase Brand Awareness, influence company value, and achieve goals. This study aims to evaluate the effectiveness of E-commerce and Digital Payment on Brand Awareness and customer satisfaction at private PDAMs. Quantitative methods were used with a sample of 98 customers and multiple linear regression analysis. The results showed that E-commerce and Digital Payment partially positively affected Brand Awareness, with t values of 4.416 and 4.656, respectively (value > t table). Simultaneously, both factors have a positive effect on Brand Awareness, with a calculated f value of 29,979 (value> f table) and a significance level of 0.000. E-commerce and Digital Payment together contribute 38.7% to increasing Brand Awareness (R square 0.568), while the rest is influenced by other factors not included in this study. Keywords— Brand Awareness; E-commerce; Digital Payment; Customer Satisfaction